ANALISIS KELAYAKAN FINANSIAL USAHA PENGOLAHAN TEMPE STUDI KASUS PADA UMKM RIZKY JAYA DI KOTA BATU - sudirman, sudirman; Tri Wulan Cahya, Utik; Farah Fadillah, Ummu; Wakiah, Nurul (BUANA SAINS, 2025)
The development of the agro-industry in Batu City has spurred the growth of Micro, Small, and Medium Enterprises (MSMEs), including those involved in tempeh processing. However, many MSMEs have not conducted comprehensive financial feasibility assessments to ensure business sustainability. This study aimed to analyze the financial feasibility of the tempeh processing business at UMKM Rizky Jaya and test its resilience to cost fluctuations through sensitivity analysis. Data were collected through in-depth interviews, field observations, and document studies. A Feasibility analysis utilized indicators such as Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), Break-Even Point (BEP), and Revenue Cost Ratio (R/C). The business generates an annual net profit of IDR 262,645,791 with an NPV of IDR 607,995,760 (at a 10% discount rate), IRR of 90%, PP of 389 days, BEP of 10,395 units, and R/C Ratio of 1.35. The tempeh processing business at UMKM Rizky Jaya is financially viable and shows strong resilience to market fluctuation risks. This study recommends the need for product diversification and technology utilization to enhance long-term competitiveness.